Development of a Predictive Model for Skin-to-Skin Contact Immediately after Birth: A Cross-Sectional Study - María Antonia Díaz-Ogallar; Antonio Hernández-Martínez; Manuel Linares-Abad; Juan Miguel Martínez-Galiano (MDPI AG, 2024)
The aim of this study was to develop and validate a predictive model for the establishment of skin-to-skin contact immediately after birth. A descriptive cross-sectional study was conducted during the last trimester of 2022 and the first trimester of 2023 with women who had given birth in Spain. A questionnaire containing sociodemographic, psychosocial, and health variables referring to the mother and the newborn, as well as the Bond and Attachment questionnaire (VAMF, for its name in Spanish) for the analysis of the mother-child bond and attachment, were administered. A multivariate analysis was performed, and areas under the ROC curve (AUC) with their 95% confidence intervals (CI) and the predictive characteristics of these models were estimated. In total, 1077 women participated. The prevalence of early skin-to-skin contact after delivery was 50.2% (468) in the derivation cohort and 49.8% (464) in the validation cohort. Multivariate analysis showed that prematurity, type of delivery, and birth experience were statistically significant, so they were included in the model (p ≤ 0.05). The predictive ability (AUC ROC) was good in both the derivation cohort, yielding 0.92 (95% CI: 0.89-0.95), and in the validation cohort, yielding 0.89 (95% CI: 0.85-0.93). This study developed a predictive model identifying factors facilitating early skin-to-skin contact between a mother and her newborn immediately after birth.